The Prados del Cervunal morainic complex: Evidence of a MIS 2 glaciation in the Iberian Central System synchronous to the global LGM - Carrasco, Rosa M.; Turu, Valenti; Soteres, Rodrigo L.; Fernandez-Lozano, Javier; Karampaglidis, Theodoros; Rodes, Angel; Ros, Xavier; Andres, Nuria; Granja-Bruna, Jose Luis; Munoz-Martin, Alfonso; Lopez-Saez, Jose Antonio; Braucher, Regis; et al. (My University, 2023)
The area of Prados del Cervunal (PC) is an intra-morainic topographic depression located at 1800 m asl in the divide or interfluve between Garganta de Gredos and Garganta del Pinar valleys (Central Gredos; Iberian Central System, ICS). Both valleys, along with the adjacent Hoya Nevada, were occupied by glaciers during the Upper Pleistocene, leading to the development of the Prados del Cervunal moraine complexes studied in this work. Using cartographic methods and morphostratigraphic analysis, the three main glacial formations established in the Regional Chrono-Evolutionary Pattern for the ICS, Peripheral Deposits (PD), Principal Moraine (PM) and Internal Deposits (ID), have been identified and mapped in this area. The chronology of these formations has been implemented by Cosmic Ray Exposure (CRE) techniques using 10Be (new data) and 26Cl (previous data, recalculated in this work) in samples from morainic boulders. With these data, the following chrono-evolutionary sequence has been established: (stage 1) local-Maximum Ice Extent (MIE), dated in 25.0&PLUSMN; 1.4 ka and corresponding to the maximum age obtained in these paleoglaciers; (stage 2) period of oscillations around the MIE, corresponding to the development of the PD Formation between-25 ka and-21 ka; (stage 3) period of readvance and sta-bilisation, dated after-21 ka (average age obtained for the PD moraines attached to PM moraines) and previous to-18 (minimum age obtained for a main crest of the PM formation); and (stage 4) onset of deglaciation dated around to-18 ka (average of ages obtained for the first main crest of the ID forma-tion). During the stages of maximum ice expansion, these three glaciers formed an Ice field whose tongues were interconnected on the PC flat by an ice transfluence system (stages 1 and 2, Plateau Glacier Period). In later stages, the ice masses were partitioned, giving rise to valley glaciers and large moraines forming morainic complexes like those of PC (stages 2, 3 and 4, Valley Glaciers Period). The local MIE and onset of deglaciation stages in this area show a good fit with the ages stablished to global level for the global Last Glacial Maximum (LGM) and the onset of the Last Glacial Termination (Termination I). They also show good correlation at local (with other areas of the ICS), peninsular (with other Iberian moun-tains) and continental (some areas of the Alps and mountains of Central Europe) level. Finally, this evolutionary sequence and its correlations allowed us to adjust and validate some units of the Regional Chrono-Evolutionary Pattern model and propose the Gredos-Pinar-Cabeza Nevada glacial system as benchmark for the glaciation of Marine Isotope Stage (MIS) 2 in the Iberian Peninsula.& COPY; 2023 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: last glacial cycle; global last glacial maximum; marine isotope stage 2; last deglaciation; morphostratigraphy; cosmic ray exposure dating; iberian central system